Non‐invasive brain stimulation for fine motor improvement after stroke: a meta‐analysis - O'Brien, A. T.; Bertolucci, F.; Torrealba‐Acosta, G.; Huerta, R.; Fregni, F.; Thibaut, A. (European journal of neurology, 2018)
The aim of this study was to determine whether non‐invasive brain stimulation (NIBS) techniques improve fine motor performance in stroke. We searched PubMed, EMBASE, Web of Science, SciELO and OpenGrey for randomized clinical trials on NIBS for fine motor performance in stroke patients and healthy participants. We computed Hedges’ g for active and sham groups, pooled data as random‐effects models and performed sensitivity analysis on chronicity, montage, frequency of stimulation and risk of bias. Twenty‐nine studies (351 patients and 152 healthy subjects) were reviewed. Effect sizes in stroke populations for transcranial direct current stimulation and repeated transcranial magnetic stimulation were 0.31 [95% confidence interval (CI), 0.08–0.55; P = 0.010; Tau2, 0.09; I2, 34%; Q, 18.23; P = 0.110] and 0.46 (95% CI, 0.00–0.92; P = 0.05; Tau2, 0.38; I2, 67%; Q, 30.45; P = 0.007). The effect size of non‐dominant healthy hemisphere transcranial direct current stimulation on non‐dominant hand function was 1.25 (95% CI, 0.09–2.41; P = 0.04; Tau2, 1.26; I2, 93%; Q, 40.27; P < 0.001). Our results show that NIBS is associated with gains in fine motor performance in chronic stroke patients and healthy subjects. This supports the effects of NIBS on motor learning and encourages investigation to optimize their effects in clinical and research settings.